Modified phenolic resin-based hard carbon material as well as preparation method and application thereof
By introducing metal ions into the phenolic resin and replacing traditional materials with glucolytic lactone and 1,2,4-phenylephrine glutamol, the problem of high preparation cost and safety threat of phenolic resin-based hard carbon materials is solved. The prepared modified phenolic resin-based hard carbon materials have high efficiency and stable battery performance.
Patent Information
- Application Number
- CN202510057523.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The preparation cost of phenolic resin-based hard carbon materials is high, and the preparation process poses a great threat to the life, health and safety of workers. The currently prepared phenolic resin-based hard carbon materials are as the negative electrode materials of the battery, such as low specific capacity, low Coulomb efficiency and poor circulation stability.
Modified phenolic resin-based hard carbon material is prepared by introducing metal ions into the phenolic and using aldehyde group-rich glualdehyde lactones containing aldehyde groups instead of formaldehyde in the traditional method, and using 1,2,4-phenylephthalene glutamol containing three phenolic hydroxyl groups and two phenolic hydroxyl groups in ortho-position to replace phenol in the traditional method. The method includes adding surfactant, ammonia water, 1,2,4-phenylatin and glucolytic lactone to the solvent for stirring reaction, then adding metal ion salt to continue the reaction, then placing the solution at the end of the reaction in a polytetrafluoroethylene liner for hydrothermal reaction, and finally graphitization reaction under an argon atmosphere in a high-temperature tube furnace to prepare a modified phenolic resin-based hard carbon material.
The thermosetting phenolic resin is achieved at a low cost, non-toxic and pollution-free preparation. The prepared modified phenolic resin-based hard carbon material has a suitable specific surface area, rich micropores and a larger graphitized layer spacing. As the negative electrode material of sodium ion battery, it has high first-time Coulomb efficiency, platform capacity and stable circulation capacity retention.
Smart Images

Figure CN119841303A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of phenolic resin-based hard carbon materials, and in particular to a modified phenolic resin-based hard carbon material and a preparation method and application thereof. Background Art
[0002] Phenolic resin has good high temperature resistance, chemical resistance, bonding strength, etc., and has a wide range of applications. At the same time, due to the advantages of simple preparation process, high residual carbon rate and easy structure control, it has always been considered as a high-quality carbon precursor. Thermoplastic phenolic resin (hydrogen-rich and oxygen-deficient) is easy to graphitize to form soft carbon materials above 1000°C, while thermosetting phenolic resin (oxygen-rich and hydrogen-deficient) is difficult to graphitize to form hard carbon materials above 1000°C due to a large amount of oxygen, and can be used as negative electrode materials for sodium ion batteries.
[0003] Traditional phenolic resins are formed by the condensation of phenol and formaldehyde under the catalytic action of acid or alkaline. However, phenol is expensive and is a Class 3 carcinogen announced by the World Health Organization's International Agency for Research on Cancer. Formaldehyde is a Class 1 carcinogen announced by the World Health Organization's International Agency for Research on Cancer. They pose a great threat to human life, health and safety during the production process.
[0004] Sodium-ion batteries are considered to be an effective supplement to lithium-ion batteries because of their similar working principles. Hard carbon materials are considered to be the most promising negative electrode materials for sodium-ion batteries because of their good low-voltage platform and sodium storage capacity. However, there are still problems such as low specific capacity, low coulombic efficiency and poor cycle stability. Although there are some technologies to improve these problems, they often cannot take all three into account. Summary of the invention
[0005] The purpose of the present invention is to provide a modified phenolic resin-based hard carbon material and a preparation method and application thereof, so as to solve the problems that the preparation cost of phenolic resin-based hard carbon materials is high, the preparation process poses a great threat to the life, health and safety of workers, and the currently prepared phenolic resin-based hard carbon materials have low specific capacity, low coulombic efficiency and poor cycle stability as battery negative electrode materials.
[0006] To achieve the above object, the present invention provides a method for preparing a modified phenolic resin-based hard carbon material, comprising the following steps:
[0007] S1. Introduce metal ions into phenolic aldehyde, add surfactant and 25% to 30% ammonia water in the solvent in sequence, add 1,2,4-pyrogallol after mixing, add glucuronolactone after dissolving, stir and react; add metal ion salt to the solution after the reaction is completed, and continue the reaction;
[0008] S2, preparing a modified phenolic resin-based material, placing the solution obtained after the reaction in step S1 into a polytetrafluoroethylene liner, moving it into a hydrothermal autoclave for reaction, and filtering, washing, and drying the product to obtain a modified phenolic resin-based material;
[0009] S3. Prepare a modified phenolic resin-based hard carbon material, transfer the prepared phenolic resin-based material to a corundum porcelain boat, and react it in a high-temperature tubular furnace under an argon atmosphere to obtain a modified phenolic resin-based hard carbon material.
[0010] Preferably, in step S1, the solvent is one or both of deionized water and ethanol, and the surfactant is one of polyethylene glycol and ethylene glycol.
[0011] Preferably, in step S1, the mass volume ratio of the solvent: surfactant: ammonia water: 1,2,4-pyrogallol: glucuronolactone: metal ion salt is 60 mL: 0.25 mL: 0-3 mL: 1.5 g: 3 g: 0.4 g.
[0012] Preferably, the metal ion salt in step S1 is one of zinc acetate, zinc chloride and zinc sulfate.
[0013] Preferably, in step S1, the metal ion salt is added and the reaction is stirred for 12 hours.
[0014] Preferably, the hydrothermal reaction conditions in step S2 are 180° C. for 24 hours.
[0015] Preferably, the reaction conditions in the argon atmosphere in step S3 are to increase the temperature to 900° C. at 5° C. / min, keep the temperature for 1 hour, and then increase the temperature to 1300° C. at 2° C. / min and keep the temperature for 3 hours.
[0016] A modified phenolic resin-based hard carbon material prepared by the method for preparing the modified phenolic resin-based hard carbon material as described above.
[0017] An application of the modified phenolic resin-based hard carbon material as described above in a sodium ion battery, wherein the modified phenolic resin-based hard carbon material is used as a negative electrode of the sodium ion battery.
[0018] Therefore, the present invention provides a modified phenolic resin-based hard carbon material and a preparation method and application thereof, and the specific technical effects thereof are as follows:
[0019] (1) The present invention creatively uses aldehyde-containing, oxygen-rich glucuron lactone to replace formaldehyde in the traditional method. The method provided by the present invention is easy to prepare thermosetting phenolic resin, and as a glucose metabolite, glucuron lactone has the advantages of low cost and non-toxicity and no pollution;
[0020] (2) The present invention uses 1,2,4-pyrogallol containing three phenolic hydroxyl groups, two of which are in the ortho position, to replace phenol in the traditional method, which is conducive to forming a coordination compound with metal ions and realizing ion doping. In addition, 1,2,4-pyrogallol is not one of the three types of carcinogens, which can reduce the harm to the human body during the production process;
[0021] (3) The modified phenolic resin-based hard carbon material prepared by the method provided by the present invention has a suitable specific surface area, abundant micropores and a larger graphitized interlayer spacing. The specific surface area of the modified phenolic resin-based hard carbon material is 451.51 m 2 / g, micropore volume is 0.217cm 3 / g;
[0022] (4) The modified phenolic resin-based hard carbon material prepared by the present invention is used as the negative electrode material of the sodium ion battery, which has an initial coulombic efficiency of 86.44%, a platform capacity of 232.8 mAh / g at a current density of 0.05 A / g, and a capacity retention rate of 83.71% after stable circulation for 1000 cycles with a coulombic efficiency of 99.97% at a current density of 1 A / g. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments of the present invention will be briefly introduced below. Obviously, the accompanying drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative labor.
[0024] Figure 1 FTIR graph of the phenolic resin synthesized in Example 1;
[0025] Figure 2 is the XPS graph of the phenolic resin synthesized in Example 1;
[0026] Figure 3 The TGA curves of the phenolic resins synthesized in Example 1, Comparative Example 1-1 and Comparative Example 1-2;
[0027] Figure 4 The SEM images of the phenolic resin-based hard carbon materials prepared in Example 1 and Comparative Example 1-1; wherein part a) and part b) are SEM images of the phenolic resin-based hard carbon materials prepared in Comparative Example 1-1; part c) and part d) are SEM images of the phenolic resin-based hard carbon materials prepared in Example 1;
[0028] Figure 5 XRD patterns of phenolic resin-based hard carbon materials prepared in Example 1 and Comparative Example 1-1;
[0029] Figure 6 This is the GCD curve of the sodium ion battery prepared in Example 2 at a current density of 0.05 A / g;
[0030] Figure 7 A bar graph comparing the slope capacity and platform capacity of the first cycle charging curve of the sodium ion battery prepared in Example 2 and Comparative Example 2-1 at a current density of 0.05 A / g;
[0031] Figure 8 The graph is a graph of the cycle number-specific capacity / coulombic efficiency of the sodium ion batteries prepared in Example 2, Comparative Example 2-1 and Comparative Example 2-2 at a current density of 1 A / g. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.
[0033] In order to make the purpose, technical scheme and advantages of the present application clearer, more thorough and complete, the technical scheme of the present invention is clearly and completely described below through the accompanying drawings and examples. The following detailed descriptions are all descriptions of the embodiments, and are intended to provide further detailed descriptions of the present invention. Unless otherwise specified, all technical terms used in the present invention have the same meaning as those generally understood by those skilled in the art to which the present application belongs.
[0034] The instruments, equipment, reagents and materials used in the examples were all obtained through commercial channels.
[0035] Example 1
[0036] A modified phenolic resin-based hard carbon material is prepared, and the specific steps are as follows:
[0037] (1) Add 0.25 mL of polyethylene glycol and 0.5 mL of 28% ammonia water to 60 mL of deionized water and stir to mix. Then add 1.5 g of 1,2,4-pyrogallol and add 3 g of glucuronolactone after it dissolves. Stir at 50 °C for 2 h. After the time is up, add 0.4 g of zinc acetate and continue stirring for 12 h.
[0038] (2) The solution after stirring in step (1) was transferred to a 100 mL polytetrafluoroethylene liner, and hydroheated at 180° C. / 24 h. The hydrothermal product was filtered, washed with deionized water, and dried at 60° C. for 24 h to obtain a phenolic resin-based material.
[0039] The Fourier transform infrared absorption spectrum (FTIR) of the obtained phenolic resin-based material is as follows: Figure 1 As shown in the figure, the results show that 1,2,4-benzenetriol is combined with glucuron lactone to successfully synthesize phenolic resin materials. The X-ray photoelectron spectroscopy (XPS) of the obtained phenolic resin-based material is shown in Figure 2As shown, the results indicate that Zn was successfully introduced into the phenolic resin via Zn-O coordination.
[0040] (3) The obtained phenolic resin-based material was transferred to a corundum porcelain boat, and in a high-temperature tube furnace, the temperature was increased to 900°C at a rate of 5°C / min under an argon atmosphere, and kept at that temperature for 1 h. The temperature was then increased to 1300°C at a rate of 2°C / min and kept at that temperature for 3 h to obtain a modified phenolic resin-based hard carbon material.
[0041] Comparative Example 1-1
[0042] A phenolic resin-based hard carbon material is prepared, and the specific steps are as follows:
[0043] (1) Add 0.25 mL of polyethylene glycol and 0.5 mL of 28% ammonia water to 60 mL of deionized water and stir to mix. Then add 1.5 g of 1,2,4-pyrogallol and add 3 g of glucuronolactone after it dissolves. Stir at 50°C for 2 h.
[0044] (2) The solution after stirring in step (1) was transferred to a 100 mL polytetrafluoroethylene liner, and hydroheated at 180° C. / 24 h. The hydrothermal product was filtered, washed with deionized water, and dried at 60° C. for 24 h to obtain a phenolic resin-based material.
[0045] (3) The obtained phenolic resin-based material was transferred to a corundum porcelain boat, and in a high-temperature tube furnace, the temperature was increased to 900°C at a rate of 5°C / min under an argon atmosphere, and kept at that temperature for 1 h. The temperature was then increased to 1300°C at a rate of 2°C / min and kept at that temperature for 3 h to obtain a phenolic resin-based hard carbon material.
[0046] Comparative Example 1-2
[0047] A glucuronolactone-based hard carbon material is prepared, and the specific steps are as follows:
[0048] (1) Add 0.25 mL of polyethylene glycol and 0.5 mL of 28% ammonia water to 60 mL of deionized water and stir to mix. Then add 3 g of glucuronolactone and stir at 50° C. for 2 h.
[0049] (2) The solution after stirring in step (1) was transferred to a 100 mL polytetrafluoroethylene liner, and hydroheated at 180°C / 24h. The hydrothermal product was filtered, washed with deionized water, and dried at 60°C for 24h to obtain the glucuronide material.
[0050] (3) The obtained glucuron lactone material was transferred to a corundum porcelain boat, and in a high-temperature tube furnace, the temperature was increased to 900°C at 5°C / min under an argon atmosphere, and kept at this temperature for 1 h. The temperature was then increased to 1300°C at 2°C / min and kept at this temperature for 3 h to obtain a glucuron lactone-based hard carbon material.
[0051] The materials (carbonized precursor materials) obtained in step (2) of Example 1, step (2) of Comparative Example 1-1 and step (2) of Comparative Example 1-2 were subjected to thermogravimetric analysis (TGA). The results are as follows: Figure 3 As shown, the results show that the carbon yield of Example 1 and Comparative Example 1-1 is improved, further indicating that glucuron-lactone and 1,2,4-benzenetriol undergo a polymerization reaction to form a phenolic resin material.
[0052] The scanning electron microscope (SEM) photos of the phenolic resin-based hard carbon material obtained in Example 1 and Comparative Example 1-1 are as follows: Figure 4 As shown, part a) and part b) are SEM images of the phenolic resin-based hard carbon material prepared in Comparative Example 1-1; part c) and part d) are SEM images of the phenolic resin-based hard carbon material prepared in Example 1. From the comparison between part a) and part c), and part b) and part d), it can be seen that the Zn introduced by Zn-O coordination plays a pore-forming role in the carbonization process, improves the porosity, increases the specific surface area, and exposes more active sites.
[0053] The X-ray diffraction (XRD) analysis of the phenolic resin-based hard carbon material obtained in Example 1 and Comparative Example 1-1 showed the following results: Figure 5 As shown, the phenolic resin-based hard carbon materials prepared in Example 1 and Comparative Example 1-1 both exhibit typical hard carbon characteristics. In comparison, the left shift of the broad peak position indicates that the Zn introduced by Zn-O coordination increases the interlayer spacing of graphitization during the carbonization process, which is conducive to better diffusion dynamics.
[0054] Example 2
[0055] The modified phenolic resin-based hard carbon material prepared in Example 1 was assembled into a sodium ion battery, and the energy storage potential and cycle stability tests were performed as follows: the modified phenolic resin-based hard carbon material prepared in Example 1 was used as the active material of the positive electrode, the sodium sheet was used as the negative electrode, and the electrolyte was 1M NaF 6 The sodium ion battery was obtained by preparing a diethylene glycol dimethyl ether (DIGLYME) solution and assembling the battery using a model 2032 button cell in an argon-protected glove box.
[0056] The prepared sodium ion battery was tested at a current density of 0.05A / g, and its GCD curve was as follows: Figure 6 As shown in Figure 1, under the appropriate specific surface area, the modified phenolic resin as a negative electrode material for sodium ion batteries has an initial coulombic efficiency of 86.44%. The slope capacity and platform capacity comparison bar graph of the first cycle charging curve is shown in Figure 1. Figure 7 As shown, the cycle number-specific capacity / Coulombic efficiency curve at a current density of 1A / g is as follows Figure 8 shown.
[0057] Comparative Example 2-1
[0058] The phenolic resin-based hard carbon material prepared in Comparative Example 1-1 was used as the active material of the positive electrode, the sodium sheet was used as the negative electrode, and the electrolyte was 1M NaF 6 The battery was assembled in an argon-protected glove box using a 2032 coin cell solution of diethylene glycol dimethyl ether (DIGLYME). The test was conducted at a current density of 0.05 A / g. The slope capacity and platform capacity comparison bar graph of the first cycle charging curve is shown in the figure below. Figure 7 As shown, the cycle number-specific capacity / Coulombic efficiency curve at a current density of 1A / g is as follows Figure 8 shown.
[0059] Depend on Figure 7 It can be seen that the phenolic resin-based hard carbon material prepared in Example 2 has a larger porosity due to the pore-forming effect, and has more sodium storage sites, which is conducive to generating more sodium storage capacity.
[0060] Comparative Example 2-2
[0061] The glucuronolactone-based hard carbon prepared in Comparative Example 1-2 was used as the active material of the positive electrode, the sodium sheet was used as the negative electrode, and the electrolyte was 1M NaF 6 The battery was assembled in an argon-protected glove box using a 2032 coin cell solution of diethylene glycol dimethyl ether (DIGLYME). The test was performed at a current density of 0.05 A / g. The cycle number-specific capacity / coulombic efficiency curve at a current density of 1 A / g is shown in FIG. Figure 8 shown.
[0062] Depend on Figure 8 By comparison, it can be seen that under the current density of 1A / g, the number of cycles of Example 2 and Comparative Example 2-1 can both reach 1000 cycles, while Comparative Example 2-2 is only close to 800 cycles, indicating that the phenolic resins synthesized in Example 2 and Comparative Example 2-1 have a stable cross-linked structure and are retained after forming hard carbon to form a stable carbon skeleton. At the same time, Example 2 has a higher cycle specific capacity after pore formation, and still has a specific capacity of 83.71% 232mAh / g after 1000 cycles.
[0063] Therefore, the present invention creatively uses aldehyde-containing, oxygen-rich glucuronolactone to replace formaldehyde in the traditional method, and uses 1,2,4-pyrogallol containing three phenolic hydroxyl groups with two phenolic hydroxyl groups in the ortho position to replace phenol in the traditional method. The provided method is easy to prepare thermosetting phenolic resin, has the advantages of low cost and non-toxicity and pollution-free; the prepared modified phenolic resin-based hard carbon material has a suitable specific surface area, abundant micropores and a larger graphitized interlayer spacing. The specific surface area of the modified phenolic resin-based hard carbon material is 451.51 m 2 / g, micropore volume is 0.217cm 3 / g; the modified phenolic resin-based hard carbon material prepared by the present invention is used as the negative electrode material of the sodium ion battery, which has an initial coulombic efficiency of 86.44%, a platform capacity of 232.8mAh / g at a current density of 0.05A / g, and a capacity retention rate of 83.71% after stable circulation for 1000 cycles with a coulombic efficiency of 99.97% at a current density of 1A / g.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a modified phenolic resin-based hard carbon material, characterized in that: The steps include: S1, introducing metal ions into phenolic aldehyde, adding surfactant and 25-30% ammonia water to the solvent in sequence, adding 1,2,4-pyrogallol after mixing, adding glucuronolactone after dissolving, stirring and reacting; adding metal ion salt to the solution after the reaction is completed, and continuing the reaction; S2, preparing a modified phenolic resin-based material, placing the solution obtained after the reaction in step S1 into a polytetrafluoroethylene liner, moving it into a hydrothermal autoclave for reaction, and filtering, washing, and drying the product to obtain a modified phenolic resin-based material; S3. Prepare a modified phenolic resin-based hard carbon material, transfer the prepared phenolic resin-based material to a corundum porcelain boat, and react it in a high-temperature tubular furnace under an argon atmosphere to obtain a modified phenolic resin-based hard carbon material.
2. The method for preparing a modified phenolic resin-based hard carbon material according to claim 1, characterized in that: In step S1, the solvent is one or both of deionized water and ethanol, and the surfactant is one of polyethylene glycol and ethylene glycol.
3. The method for preparing a modified phenolic resin-based hard carbon material according to claim 1, characterized in that: In the step S1, the mass volume ratio of the solvent: surfactant: ammonia water: 1,2,4-pyrogallol: glucuronolactone: metal ion salt is 60 mL: 0.25 mL: 0-3 mL: 1.5 g: 3 g: 0.4 g.
4. The method for preparing a modified phenolic resin-based hard carbon material according to claim 1, characterized in that: In step S1, the metal ion salt is one of zinc acetate, zinc chloride and zinc sulfate.
5. The method for preparing a modified phenolic resin-based hard carbon material according to claim 1, characterized in that: In the step S1, the metal ion salt is added and stirred to react for 12 hours.
6. The method for preparing a modified phenolic resin-based hard carbon material according to claim 1, characterized in that: The hydrothermal reaction conditions in step S2 are 180° C. for 24 hours.
7. The method for preparing a modified phenolic resin-based hard carbon material according to claim 1, characterized in that: The reaction conditions in the step S3 under an argon atmosphere are to increase the temperature to 900° C. at a rate of 5° C. / min, keep the temperature for 1 hour, and then increase the temperature to 1300° C. at a rate of 2° C. / min and keep the temperature for 3 hours.
8. A modified phenolic resin-based hard carbon material prepared by the method for preparing a modified phenolic resin-based hard carbon material according to any one of claims 1 to 7.
9. A use of the modified phenolic resin-based hard carbon material according to claim 8 in a sodium ion battery, characterized in that: The modified phenolic resin-based hard carbon material is used as the negative electrode of a sodium ion battery.
Citation Information
Patent Citations
Composite particles, manufacturing method thereof, electrode material for secondary battery, and secondary battery
CA2859113A1
High-voltage-resistant insulating sodium-ion battery adhesive tape
CN114316833A
Polyurethane foam composition and preparation method thereof
CN114716641A
Sodium-ion battery hard carbon negative electrode material and preparation method thereof
CN116022769A
Production method of melamine impregnated paper
CN116815541A
Cited By
Modified phenolic resin-based hard carbon material applied to sodium-ion battery, preparation method of modified phenolic resin-based hard carbon material and sodium-ion battery negative electrode material
CN122059396A
High-capacity long-circulation sodium ion battery negative electrode material and preparation method thereof
CN122370375A